Employment Protection and Firm Relocation: Theory and Evidence - Gerda Dewit; Holger Görg; Yama Temouri (Economica, 2019)
We examine the determinants of the decision to relocate activities abroad for firms located in OECD countries. We argue that particular firm-specific features play a crucial role for the link between employment protection and relocation. Stricter employment protection laws over time in the current production location discourage firms' relocation abroad. While larger, more productive firms and firms with higher labour intensities have, ceteris paribus, higher propensities to relocate, they also face higher exit barriers if the country from which they consider relocating has strict employment protection laws. Our predictions are supported empirically, using firm level panel data for 28 OECD countries over the period 1997-2007.
Keywords: F23; L23; J88; 330; Employment Protection; Relocation; Multinational Enterprises